Clinico-epidemiological Characteristics of Acute Covid-19 Patients in a Tertiary Care Hospital of Dhaka, Bangladesh - Hossain, Syed Zakir; Akhtaruzzaman, Md; Nusrat, Sabiha; Islam, Saiful; Hoque, Md Jewel; Ahmed, Akhlak; Islam, Mohammad Saiful (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: The COVID-19 pandemic is a catastrophe enormously affecting the whole world including Bangladesh. This disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) began in Wuhan, China, in December 2019, and since then has been spreading globally. Objectives: To find out the sociodemographic, clinical characteristics and in-hospital outcome of patients of acute COVID-19 confirmed cases in a tertiary care hospital. Methodology: It was a hospital based observational study. Consecutive samples were taken from RT-PCR positive cases (ranging from mild to severe form) admitted in COVID-19 unit of Shaheed Suhrawardy Medical College Hospital, Dhaka during the period of July 1st to August 31st 2020. Socio-demographic and clinical data were collected by using a pretested structured questionnaire. The severity of the COVID- cases was assessed based on the WHO interim guideline. Analysis was done with SPSS (Statistical Package for Social Science) version-23. Results: Total 77 cases were found valid for study according to inclusion and exclusion criteria. Male patients were predominant which was 72.7%. Mean age was found 53.32±13.48 years. The mean age was significantly higher (58.82±11.74 years) in severe group. Fever, shortness of breath (SOB), cough and body ache were the most common presenting symptoms. Body ache was significantly higher in mild & moderate group than severe group. SOB and sore throat were significantly higher in severe group (53.5% vs 79.4%) and (9.3% vs 26.5%) respectively. Diabetes 29(37.7%), hypertension 18(23.4%), CKD 16(20.8%) and hypothyroidism 16(20.8%) were most frequent co-morbidities among the patients. Diabetes, CKD, hypothyroidism and COPD were significantly higher in severe group than mild & moderate group. The mean neutrophil lymphocyte ratio (NLR) was found 1.3±0.3 in mild & moderate group and 2.3±1.0 in severe group. Mean C-reactive protein was found 6.2±2.3 mg/L in mild & moderate group and 8.5±3.9 mg/L in severe group. The mean sodium was found 143.6±7.9 mEq/L in mild & moderate group and 136.5±9.8 mEq/L in severe group. The mean potassium was found 4.7±0.7 mEq/ L in mild & moderate group and 3.9±1.2 mEq/L in severe group. Where X-ray chest (CXR) could reveal abnormalities only in 8 cases (10.4%); HRCT-chest was able to find out abnormalities in 56 cases (72.7%). Abnormal HRCT chest was found in 56 patients among them 48(87.3%) showed normal finding on chest x-ray. The difference was statistically significant between two groups. In HRCT chest abnormalities ground glass opacities (GGOs) was the most frequent observation in 33(58.93%) patients. GGOs was found 12(50.0%) in mild & moderate group and 21(65.63%) in severe group. Major complications were pneumonia 39(50.6%) and severe pneumonia 28(36.4%) respectively. Pneumonia was significant higher in mild & moderate group than severe group (76.7% vs 17.6%). Severe pneumonia was observed 27(79.4%) in severe group. The above-mentioned parameters were statistically significant (p<0.05) between two groups. 2 patients (2.6%) died among them both were in severe group and both were male. Conclusion: Male sex and middle-aged population are mostly affected by the SARS-CoV-2. SOB and sore throat were significantly higher in severe group. Where facilities available strongly suspected individuals may go for HRCTchest. High NLR and CRP as well as lower value of sodium and potassium are good predictors for the severe or critical form of disease spectrum. J Bangladesh Coll Phys Surg 2022; 40: 183-190